Theophanic "type-scenes" in the Pentateuch: visions of YHWH - DeLapp, Nevada Levi (Library of Hebrew bible/Old Testament studies, 2018)
Seeing the unseen in the Pentateuch -- To see or not to see: the appearances of God in Genesis -- Hidden in the clouds: the appearances of God in Exodus -- Cultic theophanies and the levitical theophanic type-scene: the appearances of God in Leviticus -- Theophanies (re)contextualized: the appearances of God in Numbers -- "There was no form...": re-reading the type-scenes with Deuteronomy -- Conclusions